Influence of nitrate salt solutions on seed germination dynamics of Withania coagulans (Stocks) Dunal, an important medicinal plant of the Indian Thar desert - Daiya, Kavita; Kasera, Pawan K (Bangladesh Journal of Botany, 2019)
The effect of different concentrations (0.10, 0.25, 0.50, 0.75 and 1.0%) of nitrate salt solutions, viz. Ca(NO3)2, Co(NO3)2 and KNO3, on various aspects of fresh and one-year-old seeds and the seedling growth of Withania coagulans (Stocks) Dunal, is a critically endangered medicinal plant of the Indian Thar desert was dealt with. The maximum germination percentage in fresh and one-year-old seeds was observed in 1.0 and 0.10% Co(NO3)2 solutions, respectively. The maximum root: shoot ratio in seedlings from fresh and one-year- old seeds was observed in 0.75 and 0.50% of Ca(NO3)2 solutions, respectively.